The universe of supervision: an inclusive approach within the teacher training domain - Cardoso, Mário (2017)
Social and cultural transformations pose daily challenges to the educational field, particularly with regard to its objectives, functions, roles and the performance of those involved. This naturally leads to a need for (re)thinking the training of its professionals. The present study is integrated within this framework, developed with the aim of both assessing the quality of the inclusive approach in the supervision of teacher education, as well as creating proposals for future implementation based on the results, in order to eliminate or reduce gaps and weaknesses which may be detected. Based on these objectives, the research process was developed using a quantitative approach with the higher education public institutions of Trás-os-Montes and Alto Douro (Portugal), which include the Supervised Teaching Practice course (Teacher Training) in their curricula. The study included a total of 340 participants, divided into Student Interns (n=245), Teaching Supervisors of Higher Education Institutions (n=38) and Cooperating Teachers of the Home Institutions (n=57). Questionnaires were used as the data collection instrument for each group in the sample. The literature review and data analysis demonstrate the need for rethinking the form and content used in inclusive practices in the supervision of teaching education.